Estudo da interação cardiorrespiratória e da oferta de oxigênio periférica e cerebral como moduladores da capacidade de exercício durante a aplicação do binível na coexistência da DPOC-IC - Goulart, Cássia da Luz (2023)
This thesis is composed by 3 studies that will be described below: the study I: “Non-invasive ventilation improves exercise tolerance and peripheral vascular function after high-intensity exercise in COPD-HF patients”. Aim: To evaluate the acute effects of non-invasive positive pressure ventilation (NiPPV) during high-intensity exercise on endothelial function in patients with coexisting chronic obstructive pulmonary disease (COPD) and heart failure (HF). Methods: This is a randomized, double blinded, sham-controlled study involving 14 COPD-HF patients, who underwent a lung function test and Doppler echocardiography. In two different days, patients performed incremental cardiopulmonary exercise testing (CPET) and two constant-work rate tests (80% of peak work rate from CPET) receiving Sham or NiPPV (bilevel mode - Astral 150) in a random order until the limit of tolerance (Tlim). Endothelial function was assessed using the technique flow mediated vasodilation (FMD) at three time points: 1) Baseline; 2) immediately post-exercise with NiPPV; and 3) immediately post-exercise with Sham. Results: Our patients had a mean age of 70±7 years, FEV1 1.9±0.7 L and LVEF 41±9%. NIPPV resulted in an increased Tlim (NiPPV: 130±29s vs Sham: 98±29s p=0.015) and SpO2 (NiPPV: 94.7±3.5% vs Sham: 92.7±5.2% p=0.03). Also, NiPPV was able to produce a significant increase in FMD (%) (NiPPV: 9.2±3.1 vs Sham: 3.6±0.7, p<0.05), FMD (mm) (NiPPV: 0.41±0.18 vs Sham: 0.20±0.11, p<0.05), Blood flow velocity (NiPPV: 33±18 vs Baseline: 20±14, p<0.05) and shear stress (SS) (NiPPV: 72±38 vs Baseline: 43±25, p<0.05). We found correlation between Tlim vs. ∆SS (p=0.03; r=0.57). Univariate-regression analysis revealed that increased SS influenced 32% of Tlim during exercise with NiPPV. Conclusion: The use of NiPPV during high-intensity exercise can acutely modulate endothelial function and improve exercise tolerance in COPD-HF patients. In addition, the increase of SS positively influences exercise tolerance. Study II: “Can non-invasive ventilation modulate cerebral, respiratory, and peripheral muscle oxygenation during high-intensity exercise in patients with COPD-HF?” Aim: To evaluate the effect of non-invasive positive pressure ventilation (NIPPV)on (1) metabolic, ventilatory, and hemodynamic responses; and (2) cerebral (Cox),respiratory, and peripheral oxygenation when compared with SHAM ventilation during the high-intensity exercise in patients with coexisting chronic obstructive pulmonary disease (COPD) and heart failure (HF). Methods and Results: On separate days, patients performed incremental cardiopulmonary exercise testing and two constant-work rate tests receiving NIPPV or controlled ventilation (SHAM) in random order until the limit of tolerance (Tlim). During exercise, oxyhemoglobin (OxyHb+Mb) and deoxyhemoglobin (DeoxyHb+Mb) were evaluated in the intercostal and vastus lateralis muscles and cerebral oxygenation in the prefrontal region using near-infrared spectroscopy (Oxymon, ArtinisMedical Systems, Einsteinweg, The Netherlands). NIPPV associated with high-intensity exercise caused a significant increase in exercise tolerance, peak oxygen consumption (V̇O2inmlO2·kg−1·min−1), minute ventilation peak (V̇E in ml/min), peak peripheral oxygen saturation (SpO2, %), and lactate/tlim (mmol/s) when compared with SHAM ventilation. In cerebral, respiratory, and peripheral muscles, NIPPV resulted in a lower drop inOxyHb+Mb (p < 0.05) and an improved deoxygenation response DeoxyHb+Mb (p<0.05) from the half of the test (60% of Tlim) when compared with SHAM ventilation. Conclusion: Non-invasive positive pressure ventilation during constant work-rate exercise led to providing the respiratory muscle unloading with greater oxygen supply to the peripheral muscles, reducing muscle fatigue, and sustaining longer exercise time in patients with COPD-HF. Finally Study III: Exercise oscillatory breathing in heart failure with reduced ejection fraction: clinical implication. Aim: I) to evaluate the impact of exertional oscillatory ventilation (EOV) in patients with heart failure (HF) with reduced left ventricular ejection fraction (HFrEF) during cardiopulmonary exercise testing (CPET)compared with patients without EOV (N-EOV); II) to identify the influence of EOV persistence (P-EOV) and EOV disappearance (D-EOV) during CPET on the outcomes of mortality and hospitalization in HFrEF patients; and III) to identify further predictors of mortality and hospitalization in patients with P-EOV. Methods and results: 315 stable HFrEF patients underwent CPET and were followed for 35 months. We identified 202 patients N-EOV and 113 patients with EOV. Patients with EOV presented more symptoms (NYHA III: 35% vs. N-EOV 20%, p<0.05), worse cardiac function (LVEF: 28±6 vs. N-EOV 39±1, p<0.05), higher minute ventilation/carbon dioxide production (V̇E/V̇CO2 slope: 41±11 vs. N-EOV 37±8, p<0.05) and a higher rate of deaths (26% vs. N-EOV 6%, p<0.05) and hospitalization (29% vs. N-EOV 9%, p<0.05). P-EOV patients had more severe HFrEF (NYHA IV: 23% vs D-EOV: 9%, p<0.05), had worse cardiac function (LVEF: 24±5 vs. D-EOV: 34±3, p<0.05) and had lower peak oxygen consumption (V̇O2) (12.0±3.0 vs D-EOV: 13.3±3.0 mlO2.kg-1.min-1, p<0.05). Among P-EOV, other independent predictors of mortality were V̇E/V̇CO2 slope ≥36 and V̇O2 peak≤12 mlO2.kg-1.min-1; a V̇E/V̇CO2 slope≥34 was a significant predictor of hospitalization. Kaplan-Meier survival analysis showed that HFrEF patients with P-EOV had a higher risk of mortality and higher risk of hospitalization (p<0.05) than patients with D-EOV and N-EOV. Conclusion: In HFrEF patients, persistent EOV during exercise had a strong prognostic role. In P-EOV patients, V̇E/V̇CO2 ≥36 and V̇O2 peak≤12 mlO2.kg-1.min-1 were identified as indicators of negative prognosis.